Publication - Augustan Reprint Society; University of California (Los Angeles) Center for 17th- & 18th-Century Studies; William Andrews Clark Memorial Library ([Los Angeles s.n.], 1997)
Irregular
"Reprinted with the permission of the Augustan Reprint Society [by] Kraus Reprint Corporation, New York, 1967."
Annual bibliography of English language and literature 0066-3786
MLA international bibliography of books and articles on the modern languages and literatures (Complete edition) $x0024-8215
Published for the William Andrews Clark Memorial Library and the UCLA Center for Seventeenth- and Eighteenth-Century Studies, 1995-.
Keywords: English literature -- Facsimiles. -- Early works to 1800.; English literature -- Facsimiles. -- 19th century